Assessing the Performance of Off-Grid Solar Photovoltaic Power Plants in Supporting Aquaponics Systems - Siti Diah Ayu Febriani; Abdurrasyid Masyhuri Alqarana; Michael Joko Wibowo; Ahmad Fahriannur (Faculty of Engineering, Andi Djemma University, 2024)
In an aquaponics system, the electricity produced by photovoltaic solar power (PLTS) is stored in batteries and used to power the water pumps. Using natural microorganisms to transform fish waste into plant nutrients, aquaponics is a cultivation method that blends fish and plant cultivation. The aquaponics system helps reduce the amount of trash released into the environment and is beneficial to the environment. The main goal of this study is to evaluate an off-grid PLTS system's functionality as a DC water pump power source in an aquaponics setting. This study's goal is to evaluate how well the PLTS operates when powering the DC water pump that circulates water in the aquaponics system.According to performance tests, the off-grid PLTS generates an average energy of 503.8 Wh, which is enough to power the DC pump for 20 hours a day of water circulation. The water pump uses only 382.6 Wh of electricity each day. With an average solar panel efficiency of 4.97%, an average solar charge controller (SCC) efficiency of 60.51%, and an average pump efficiency of 79.91%, the Off-grid PLTS demonstrates efficiency. With a daily solar irradiation of 7.8 kWh/m2, the average energy loss in the solar panel is 5.29 kWh/kWp, whereas the average energy loss in the system is 0.10 kWh/kWp. All things considered, these results provide insight into how well the Off-grid PLTS functions as a power source for the DC water pump in an aquaponics system.